Laboratory manual in police photography - Nabe, Nestor C.; Cardenas, Andre A.; Malibiran, Ivy, Q. (Philippines; Wisemans Books Trading, 2021)
This Laboratory manual includes exercises.
Includes Bibliographical references.
English Text.
Keywords: Police Photography-Laboratory Manual